Row-wise substitution of F1 hybrid maize (Zea mays L. cv. C-909) with its segregating F2 generation - Paudel, Mina N.; Lales, Joveno S. (2006)
Three mixed stands corresponding to three levels of partial substitution of the F1 generation of C-909 (a single-cross hybrid) with its segregating F 2 generation, and pure stands of the two generations were evaluated for agronomic performance. Substitution was carried out by varying the row allocation for each generation, e.g., 3:1 (25%), 2:2 (50%) and 1:3 (75% substitution). Grain yield obtained from each mixed stand was not significantly different from the yield of the F1 hybrid. Full substitution, however, led to significant yield reduction by 29% or 1,248 kg ha-1. Frequency distribution analysis revealed the dynamics of grain weight per plant and other ear traits, indicating the presence of a compensatory mechanism, the expression of which was probably influenced by the microclimate. Future experiments similar to this study should include characterization of the microclimate in order to understand the dynamics of individual plant performance in relation to grain yield.
Keywords: Corn--Hybridization.